STRATEGI PEMASARAN USAHA KULINER KOBER MIE SETAN JALAN KARIMATA NO. 67 KOTA JEMBER - Siti Maria Ulfa; Joko Widodo (Economic Education, University of Jember, 2015)
Marketing strategy is the company's plan to develop a product or service which is accordance with the stated goals of the company. This research had to describe the marketing strategy of culinary business of kober mie setan that located at Karimata street 67 Jember. This type of research used is descriptive qualitative approach. The research location was determined by using purposive area method was held in kober mie setan that located in Karimata Street 67 Jember city. Analysis of the data in this study consisted of data reduction, data presentation, and conclusion Based on this research, it can be know that the kober mie setan that located at Karimata street 67 jember is one of the culinary business that implemented several marketing strategies for their culinary business There were four marketing strategies used by kober mie setan for their culinary business, such as: product strategy, area strategy, pricing strategy and promotionstrategy.